Visualizing histone H4K20me1 in knock-in mice expressing the mCherry-tagged modification-specific intracellular antibody - Yuko Sato; Maoko Takenoshita; Miku Ueoka; Jun Ueda; Kazuo Yamagata; Hiroshi Kimura (Histochemistry and Cell Biology, 2024)
During development and differentiation, histone modifications dynamically change locally and globally, associated with transcriptional regulation, DNA replication and repair, and chromosome condensation. The level of histone H4 Lys20 monomethylation (H4K20me1) increases during the G2 to M phases of the cell cycle and is enriched in facultative heterochromatin, such as inactive X chromosomes in cycling cells. To track the dynamic changes of H4K20me1 in living cells, we have developed a genetically encoded modification-specific intracellular antibody (mintbody) probe that specifically binds to the modification. Here, we report the generation of knock-in mice in which the coding sequence of the mCherry-tagged version of the H4K20me1-mintbody is inserted into the Rosa26 locus. The knock-in mice, which ubiquitously expressed the H4K20me1-mintbody, developed normally and were fertile, indicating that the expression of the probe does not disturb the cell growth, development, or differentiation. Various tissues isolated from the knock-in mice exhibited nuclear fluorescence without the need for fixation. The H4K20me1-mintbody was enriched in inactive X chromosomes in developing embryos and in XY bodies during spermatogenesis. The knock-in mice will be useful for the histochemical analysis of H4K20me1 in any cell types.

Distribution and Effects of Selenoneine by Ingestion of Extract from Mackerel Processing Residue in Mice - Takuya Seko; Yoko Sato; Michiko Kuniyoshi; Yuko Murata; Kenji Ishihara; Yumiko Yamashita; Sanjuro Fujiwara; Tomohiro Ueda; Michiaki Yamashita (Marine Biotechnology, 2023)

Ex vivo chemosensitivity assay using primary ovarian cancer organoids for predicting clinical response and screening effective drugs - Yu Ito; Jumpei Kondo; Masamune Masuda; Shinya Matsuzaki; Kunishige Onuma; Mizuki Kanda; Yuko Watanabe; Hitomi Sakaguchi; Kiyoshi Yoshino; Yutaka Ueda; Shoji Kamiura; Tadashi Kimura; et al. (Human Cell, 2022)

Risk factors for infertility treatment-associated harassment among working women: a Japan-Female Employment and Mental health in assisted reproductive technology (J-FEMA) study - Yuito Ueda; Motoki Endo; Keiji Kuroda; Kiyohide Tomooka; Yuya Imai; Yuko Ikemoto; Kiyomi Mitsui; Setsuko Sato; Atsushi Tanaka; Rikikazu Sugiyama; Koji Nakagawa; Yuichi Sato; et al. (International Archives of Occupational and Environmental Health, 2022)

Suitability of Japanese codling as a raw material for surimi-based products revealed by primary sequence analysis of myosin heavy chain and thermal gel properties - Shugo Watabe; Daisuke Ikeda; Takaki Mashiro; Yuko Kagetakubo; Yoshihiro Takahashi; Misaki Uemura; Nanami Mizusawa; Hiroki Koyama; Ko Yasumoto; Mitsuru Jimbo; Nobuhiro Kan-no; Tomohiro Ueda; et al. (Fisheries Science, 2020)

Biomonitoring method for neonicotinoid insecticides in urine of non-toilet-trained children using LC-MS/MS - Jun Ueyama; Arisa Aoi; Yuko Ueda; Naoko Oya; Yuka Sugiura; Yuki Ito; Takeshi Ebara; Michihiro Kamijima (Food Additives & Contaminants: Part A, 2020)

Effects of processing and cooking on the reduction of dinotefuran concentration in Japanese rice samples - Minae Watanabe; Jun Ueyama; Eiji Ueno; Yuko Ueda; Masaya Oda; Yuko Umemura; Takashi Tanahashi; Yoshitomo Ikai; Isao Saito (Food Additives & Contaminants: Part A, 2018)

Differentiation of Oligodendrocytes from Mouse Induced Pluripotent Stem Cells Without Serum - Sachiyo Misumi; Ruriko Nishigaki; Yoshitomo Ueda; Yoko Watanabe; Yuko Shimizu; Akimasa Ishida; ChaGyun Jung; Hideki Hida (Translational Stroke Research, 2013)

Hybrid lethality of cultured cells of an interspecific F1 hybrid of Nicotiana gossei Domin and N. tabacum L. - Masanobu Mino; Yuko Misaka; Junko Ueda; Ken’ichi Ogawa; Masayoshi Inoue (Plant Cell Reports, 2005)

Abstract of Poster Presentation - Hiroshi Uchida; Tetsuo Maruyama; Jkuko Sugiura; Takashi Kajitani; Touru Arase; Masanori Ono; Takashi Nagashima; Hirotaka Masuda; Hironori Asada; Yasunori Yoshimura; Soichiro Saito; Mila Ghosh; et al. (Human Cell, 2005)

The Distribution of Molybdenum in the Tissues of Wild Ducks - Mariko Mochizuki; Rei Sasaki; Yuko Yamashita; Mayumi Akinaga; Nana Anan; Sakura Sasaki; Ryo Hondo; Fukiko Ueda (Environmental Monitoring and Assessment, 2002)

Circadian and senescence-enhanced expression of a tobacco cysteine protease gene - Tadamasa Ueda; Shigemi Seo; Yuko Ohashi; Junji Hashimoto (Plant Molecular Biology, 2000)